Natural Material-Based Interventions for Pre-literacy Development in Kindergarten Children with Intellectual Disabilities - Wati, Luh Erna; Azizah, Nur (Papanda Publisher, 2025)
Children with intellectual disabilities face significant challenges in developing pre-literacy skills, which are foundational for future academic success. Traditional teaching methods often prove inadequate for addressing their unique learning needs, necessitating innovative approaches that engage multiple sensory modalities. This study investigated the effectiveness of natural material-based concrete media in enhancing pre-literacy capabilities among kindergarten children with intellectual disabilities. A classroom action research design following Kemmis and McTaggart's cyclical model was implemented over two cycles, each consisting of two sessions. Two kindergarten children aged 5-6 years with mild to moderate intellectual disabilities participated in the intervention. Pre-literacy skills were assessed using systematic observation instruments measuring letter recognition, phonological awareness, and basic writing abilities. The intervention utilized natural materials including seeds, leaves, stones, and sand for hands-on letter formation and syllable construction activities. Data collection occurred at baseline and after each intervention cycle, with assessment scores calculated as percentages of maximum possible performance. Both participants demonstrated substantial improvements in pre-literacy skills. Participant A.B progressed from 25% baseline performance to 84.09% post-intervention, while participant A.C improved from 25% to 88.63%. Both children exceeded the established 75.1% success criterion for independent skill demonstration. Qualitative observations revealed increased engagement, sustained attention, and enhanced confidence during learning activities. The multisensory approach facilitated letter recognition, phonological awareness development, and basic pre-writing skill acquisition. The findings validate the effectiveness of natural material-based interventions for developing pre-literacy skills in children with intellectual disabilities. The results support multisensory learning theories and demonstrate the practical applicability of cost-effective, environmentally sustainable educational approaches. The intervention's success suggests significant potential for inclusive education practices, particularly in resource-limited settings where natural materials offer accessible alternatives to commercial teaching aids.